The Relationship Between Teacher Professionalism And Student Success In Learning In Class V - Nabila Nur Rizqiyah (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This research aims to determine the relationship between teacher professionalism and student success in studying at Madrasah Ibtidaiyah Al Ittihad Semowo. Methodology: This research uses a quantitative approach with field research and the research subjects are 30 students from 30 members of Madrasah Ibtidaiyah Al Ittihad Semowo, meaning 100% of the population was taken. This research uses a research instrument in the form of a questionnaire. Data collection techniques using observation, questionnaires and documentation. The data analysis uses the product moment coefficient formula. Main Findings: Research findings show that there is a significant relationship between teacher professionalism and student learning success. This can be seen from the findings which show that the professional value of teachers is known to be in the high category as many as 1 student or (60%), the medium category as many as 11 students or (36.66%), while the low category as many as 1 student or (3.33%). Then the results of the student success questionnaire in learning showed that the high category was 3 students or (10%), the medium category was 20 students or (66.66%), while the low category was 7 students or (23.33%). Then, to find out the relationship or influence, it is calculated using the product moment coefficient formula which is known as the calculated rxy value = 0.236. Novelty/Originality of this study: The novelty of this research lies in the local and specific context that has rarely been explored in previous research. Most previous studies tend to focus on public schools and higher levels of education, while this research provides insight into the dynamics at play in Madrasah Ibtidaiyah, which has unique characteristics and challenges.